2017
DOI: 10.1103/physrevd.95.114012
|View full text |Cite
|
Sign up to set email alerts
|

Very narrow excited Ωc baryons

Abstract: Recently LHCb reported the discovery of five extremely narrow excited Ω c baryons decaying into Ξ + c K − . We interpret these baryons as bound states of a c-quark and a P -wave ss-diquark. For such a system there are exactly five possible combinations of spin and orbital angular momentum. The narrowness of the states could be a signal that it is hard to pull apart the two s-quarks in a diquark. We predict two of spin 1/2, two of spin 3/2, and one of spin 5/2, all with negative parity. Of the five states two c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
151
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(162 citation statements)
references
References 57 publications
(125 reference statements)
10
151
1
Order By: Relevance
“…A simpler interpretation that they are p-wave or radial and p-wave excitations of the ss-diquark c-quark system has been put forward in Refs. [18][19][20][21][22][23]. Both radial and p-wave excitations have been also studied in the framework of the QCD sum rules [24][25][26][27][28], in a phenomenological approach [29] and on the lattice [30].…”
Section: Introductionmentioning
confidence: 99%
“…A simpler interpretation that they are p-wave or radial and p-wave excitations of the ss-diquark c-quark system has been put forward in Refs. [18][19][20][21][22][23]. Both radial and p-wave excitations have been also studied in the framework of the QCD sum rules [24][25][26][27][28], in a phenomenological approach [29] and on the lattice [30].…”
Section: Introductionmentioning
confidence: 99%
“…While one may also expect that the next-to-lowest state in our model may correspond for the observed Ω c (3000) 0 , since once the values of coupling strength constants for Goldstone boson exchange are taken to be 0.9 times of the ones given in [19,21,22], the resulting energy for the next-to-lowest state is 2980 MeV, while the three higher states almost keep as what they are. The Ω 0 c resonances have also been investigated by using various of quark models [7,8,10,12,16] since the observation by LHCb collaboration. In [7,8,16], the Ω 0 c states are interpreted as system with one diquark and one charm quark, and the parities for all the five observed states are assigned to be negative, but with different spin quantum numbers.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…The Ω 0 c resonances have also been investigated by using various of quark models [7,8,10,12,16] since the observation by LHCb collaboration. In [7,8,16], the Ω 0 c states are interpreted as system with one diquark and one charm quark, and the parities for all the five observed states are assigned to be negative, but with different spin quantum numbers.…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ref. [4], Karliner and Rosner suggested that the parity was negative for all of the five states: two J P ¼ 1/2 − states [Ω c ð3000Þ 0 and Ω c ð3050Þ 0 ], two J P ¼ 3/2 − states [Ω c ð3066Þ 0 and Ω c ð3090Þ 0 ], and one J P ¼ 5/2 − state [Ω c ð3119Þ 0 ]. These exciting announcements and the theoretical work along with the pentaquarks P þ c discovered also by the LHCb Collaboration in 2015 [5] have brought us more understanding of the world of microcosmic particles.…”
Section: Introductionmentioning
confidence: 99%